(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Polyphony has conquered the linguistic landscape, and linguists admit that there are speeches that convey many voices, that hear others, those of the speaker.This polyphonic aspect can be seen both at the level of the interpretation of the discourse and at the level of the construction of the statement. According to the ScaPoLine, some language markers carry instructions indicating "voices" that are not attributable to the speaker alone. In this study, as part of the discourse analysis, we propose an analysis of two polyphonic markers (the negation and the concessive connector but) following the ScaPoLine. We will try to identify the different points of view coming from the linguistic construction of the statements denied and those containing the but, and then contextualize these voices in order to saturate them by attributing to them discourse movements that are responsible of them. Therefore, through our study our objective is to identify linguistically the Polyphonic tone of the Djurdjurassic show Bled. KEYWORDS: Polyphony- ScaPoLine – polyphonic markers- negation- concessive connector but